Profil Keterampilan Berbicara dan Menulis Bahasa Jawa Banten pada Siswa Kelas V SDN Kota Bumi Cilegon - Nisa, Khairun; Yuliana, Rina; Rakhman, Patra Aghtiar (Jurnal Simki Pedagogia, 2026)
This study aims to describe the profile of Bantenese speaking and writing skills in fifth grade students at SDN Kota Bumi, Cilegon, Banten. Considering the declining use of regional languages ​​among the community due to the influence of foreign cultures and the presence of contemporary languages, students tend to prefer to follow trends and use contemporary languages ​​so as not to be considered old-fashioned. This study uses a qualitative approach with a descriptive method, where the research subjects consisted of fifth grade students, the principal, and the local content teacher of Bantenese Javanese, which involved interviews, observations, and documentation for data collection. The data obtained were analyzed systematically through three main stages, namely data reduction, data presentation, and drawing conclusions, to obtain an accurate picture and in accordance with the real conditions in the school. Furthermore, the data were tested for validity using credibility, transferability, dependability, and certainty testing techniques. The results of the study indicate that the description of Bantenese speaking and writing skills can improve regional language skills in fifth grade students, they are already capable and are at the development stage. With the support and attention from schools, parents, and the surrounding environment, the use of Bantenese Javanese among students is slowly increasing, so that it can preserve culture and ensure that regional languages ​​continue to exist and do not become extinct, as well as forming students who are polite and courteous.